Classroom Culture When Students are Reluctant to Learn Online: Student Dissent Behaviors Explained by Their Self-Efficacy, Control of Learning, and Intrinsic Motivation - Goke, Ryan; Berndt, Maranda; Rocker, Kenneth (Frontiers in Communication, 2021)
Student beliefs about classroom culture, instructor behaviors, and their own abilities to learn significantly influence their academic engagement. COVID-19 has drastically altered the classroom environment, forcing many students into a virtual learning platform they may not have preferred or felt comfortable with. Whether it is the fault of the instructor or the environment, students who are dissatisfied engage in instructional dissent. This study examined the influence of instructor clarity, instructor relevance, self-efficacy, intrinsic motivation, distributive justice, procedural justice, and interactional justice on student dissent. The data supported six modified models, indicating a significant difference between students’ expressive, rhetorical, and vengeful dissent behaviors based on whether or not they were enrolled in their preferred learning platform.